2000
DOI: 10.1161/01.cir.101.6.e76
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Inhibitors of Platelet Glycoprotein IIb/IIIa in Clinical Development

Abstract: Activation of the platelet glycoprotein (GP IIb/IIIa) receptor on the platelet surface is the final pathway of platelet aggregation, regardless of the initiating stimulus. Inhibitors of GP IIb/IIIa receptors include monoclonal antibodies (abciximab) against this receptor and peptidic and nonpeptidic synthetic specific receptor blockers. Abciximab exchanges between and binds to platelets for as long as 2 weeks, whereas synthetic GP IIb/IIIa inhibitors inhibit ex vivo platelet aggregation for only a few hours af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 34 publications
0
17
0
1
Order By: Relevance
“…Therefore, inhibition of aggregation may increase the risk of bleeding, in agreement with studies using other antiplatelet agents. 26,27 The roles of GP Ib and of GP IIb/IIIa in the formation of a platelet-dependent thrombus are complementary. Indeed, we found that combined inhibition has a more pronounced effect on in vitro platelet accumulation onto collagen in a flow chamber and on the prevention of CFRs in the baboon.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inhibition of aggregation may increase the risk of bleeding, in agreement with studies using other antiplatelet agents. 26,27 The roles of GP Ib and of GP IIb/IIIa in the formation of a platelet-dependent thrombus are complementary. Indeed, we found that combined inhibition has a more pronounced effect on in vitro platelet accumulation onto collagen in a flow chamber and on the prevention of CFRs in the baboon.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of platelets to the pathogenesis of potentially fatal ischemic and/or thromboembolic events, including stroke, myocardial infarct, and pulmonary embolism, is well documented [137]. Therefore, the discovery of effective modulators of platelet function that can prevent thrombus formation is the focus of intensified efforts in translational hematology and cardiovascular biology research [137][138][139][140][141][142][143][144][145][146][147][148]. Such agents may Int Rev Immunol Downloaded from informahealthcare.com by Nyu Medical Center on 06/08/15…”
Section: Thromboembolism and Lfm-a13mentioning
confidence: 99%
“…Additional trials including a larger numbers of patients in a prospective double-bind randomized study will be required to confirm these results and to assess the effects of combining meloxicam with other newer antithrombotic therapies. 32,33 …”
Section: Circulation July 9 2002mentioning
confidence: 99%